Organizational culture and teacher work habits in selected schools in Cebu province - Orge, Linrose L.; Cruz, Genalie A. Dela; Neri, Remcil B.; Bergamo, Ma. Adela B. (Edelweiss Applied Science and Technology, 2025)
This study examined the relationship between the technical and social systems and teachers’ implementation habits in selected high schools in Cebu Province. Using a descriptive-correlational design, the research analyzed how the integration of technical components Sort, Set in Order, Shine, Standardize, Sustain, and Safety, and the social component Spirit influences teachers’ classroom preparation, timeliness, and collaboration. Results revealed strong and significant positive correlations between both systems and all dimensions of implementation habits, indicating that as teachers adopt organized, standardized, and collaborative practices, their work efficiency and consistency improve. Among the technical factors, Shine and Standardize exhibited the highest correlations with classroom preparation, while Spirit demonstrated the strongest association with timeliness and collaboration. These findings affirm the interdependence of technical discipline and social cohesion in enhancing teachers’ performance. The study concludes that a well-balanced socio-technical system fosters sustainable behavioral habits and organizational productivity. It recommends that schools institutionalize the 5S principles alongside team-based support systems to sustain quality and efficiency. The results provide empirical support for socio-technical systems theory in educational settings and offer practical insights for improving teaching environments through integrated technical and social interventions.